BEYOND HEALTH INFORMATION TRANSPARENCY: REPRODUCTIVE JUSTICE, BIOPOWER, AND WOMEN’S AUTONOMY IN INDONESIA - Kadek Cahya Susila Wibawa; Salwa Putri Hardiyan; Henny Juliani (Jurnal Hukum Progresif, 2026)
In Indonesia, transparency in reproductive health information has increasingly been promoted as a legal and policy strategy to address reproductive injustice and strengthen women’s rights. Through instruments such as the Public Information Disclosure Act and Law No. 17 of 2023 on Health, the state formally recognises women’s access to information regarding contraception, pregnancy, reproductive services, and health rights. However, this study critically examines whether transparency genuinely expands women’s reproductive autonomy or instead reproduces subtle forms of governance over women’s reproductive bodies. Employing a socio-legal approach, this study combines normative analysis of legal frameworks with critical discourse analysis to examine how women are constructed as legal subjects within Indonesia’s reproductive health regime. The analysis is guided by feminist legal theory, Foucauldian biopolitics, and epistemic justice to explore the relationship between information, power, and reproductive decision-making. The findings reveal that legal recognition of reproductive health information does not automatically generate substantive autonomy. Although women may formally obtain reproductive knowledge, their ability to exercise meaningful choices remains constrained by patriarchal decision-making structures, unequal access to healthcare services, bureaucratic barriers, and the dominance of medical expertise. Transparency may therefore create an appearance of empowerment while simultaneously reinforcing institutional authority exercised by the state and healthcare systems. This study argues that reproductive justice requires more than expanding access to information; it requires transforming the power relations that determine who can access, interpret, and utilise reproductive knowledge. As an alternative framework, this study proposes epistemic sovereignty, understood as women’s right to define, manage, and control reproductive knowledge according to their own circumstances. Genuine reproductive autonomy can only emerge when women are recognised not as passive recipients of information but as authoritative subjects within a rights-based and accountable reproductive health governance system.